Strategi Komunikasi Massa BEM KM IPB dalam Melakukan Penyebaran Informasi Akademik - Aisyah Rizky Amali; Suparman, Suparman; Yafnida Julia; Salwa Putri (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2025)
This research analyzes the mass communication strategies implemented by the IPB Student Family Student Executive Board (BEM KM) in disseminating academic information to students. BEM KM IPB acts as an intermediary who filters, distributes and packages important information from the campus to increase accessibility for students. This research uses a descriptive qualitative approach, data was obtained through interviews and literature study. The findings show that the use of social media, especially Instagram, as the main platform is based on students' preferences for being more active on this media, as well as the application of the agenda setting concept which focuses on main academic issues. The mass communication strategy used by BEM KM IPB is very good in achieving the goal of disseminating information through attractive content packaging, even though there are challenges. This research provides insight into the optimization of mass communication strategies by student organizations in the academic environment as well as recommendations for improvement through collaboration and media innovation.